2010
DOI: 10.3791/2249
|View full text |Cite
|
Sign up to set email alerts
|

<em>In vivo</em> Imaging of Intact <em>Drosophila</em> Larvae at Sub-cellular Resolution

Abstract: Recent improvements in optical imaging, genetically encoded fluorophores and genetic tools allowing efficient establishment of desired transgenic animal lines have enabled biological processes to be studied in the context of a living, and in some instances even behaving, organism. In this protocol we will describe how to anesthetize intact Drosophila larvae, using the volatile anesthetic desflurane, to follow the development and plasticity of synaptic populations at sub-cellular resolution [1][2][3] . While ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
(14 reference statements)
1
16
0
Order By: Relevance
“…Next, larvae were mounted in a chamber originally designed for in vivo imaging and imaged within 15 min on a Zeiss LSM 710 confocal microscope. Details on the construction of the chamber and larvae mounting have been previously described (Fuger et al 2007; Zhang et al 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Next, larvae were mounted in a chamber originally designed for in vivo imaging and imaged within 15 min on a Zeiss LSM 710 confocal microscope. Details on the construction of the chamber and larvae mounting have been previously described (Fuger et al 2007; Zhang et al 2010). …”
Section: Methodsmentioning
confidence: 99%
“…The prepupa was paralyzed using levamisole. Similar methods can be used for larvae that need to be paralyzed or anesthetized, and are therefore studied in closed mounting arrangement with such agents added (Liu et al, 2012; Zhang et al, 2010). …”
Section: Live Imagingmentioning
confidence: 99%
“…However, this is not technically feasible due to the small size of AZs and the rapid locomotion that larvae undergo, preventing generation of P r maps in intact moving animals. Instead, we employed an alternative approach to repeatedly image the same NMJ at muscle 26 directly through the cuticle of intact larvae during anesthesia (Andlauer and Sigrist, 2012; Fouquet et al, 2009; Füger et al, 2007; Rasse et al, 2005; Zhang et al, 2010). Using this technique, we found that anesthesia eliminated action potential induced release and the associated GCaMP signals, preventing direct P r measurements in anesthetized larvae.…”
Section: Resultsmentioning
confidence: 99%